PENERAPAN E-GOVERNMENT MELALUI SISTEM MANAJEMEN APARATUR RESPONSIF DAN TERPADU (SMART) PADA BADAN KEPEGAWAIAN DAERAH PROVINSI RIAU - Yahdili Rohman; Abdul Sadad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
SMART is the implementation of e-Government in improving service in the field of staffing within the Riau Provincial Government. The purpose of this study is to find out and analyze the application of the Integrated and Responsive (SMART) Apparatus Management System at the Riau Province Regional Personnel Agency. The theoretical concept used is E-Government Implementation that uses the Rianto & Lestari theory with indicators of Hardware and Software, Data and Information, HR and Attitude, and Communication. This study uses qualitative research methods with descriptive. Data collection about this program researchers used observation, interview and documentation techniques. In selecting informants as sources of information researchers used the Snowball Sampling technique. In the implementation of E-Government through SMART at the Riau Province Regional Personnel Agency the situation in the field shows that there are still many civil servants who still do not know the mechanism and workflow from SMART, limited infrastructure and SMART have not been connected with BKN's application. The results of the study show that the implementation of E-Government has been carried out as well as possible but in the implementation phase can not be separated from the factors that influence in the form of facilities and infrastructure, socialization and availability of legal basis. Keywords : Implementation, E-Government, SMART.